2020
DOI: 10.3390/jpm11010008
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predicting the WHO/ISUP Nuclear Grade of Clear Cell Renal Cell Carcinoma by Computed Tomography-Based Radiomics Features

Abstract: Nuclear grade is important for treatment selection and prognosis in patients with clear cell renal cell carcinoma (ccRCC). This study aimed to determine the ability of preoperative four-phase multiphasic multidetector computed tomography (MDCT)-based radiomics features to predict the WHO/ISUP nuclear grade. In all 102 patients with histologically confirmed ccRCC, the training set (n = 62) and validation set (n = 40) were randomly assigned. In both datasets, patients were categorized according to the WHO/ISUP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
(27 reference statements)
0
19
1
Order By: Relevance
“…Most previous studies constructed ML models only based on CT radiomics features, which ignored the importance of traditional clinical and radiological information [ 26 , 41 , 44 ]. In our study, some parameters with clinical and radiological information that have the potential to be risk factors in the WHO/ISUP nuclear grade of CCRCC determined by multivariate regression model were fed into ML model, and the radiomics features combined with the clinicoradiological characteristics showed a better performance for the discrimination of CCRCC grades.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies constructed ML models only based on CT radiomics features, which ignored the importance of traditional clinical and radiological information [ 26 , 41 , 44 ]. In our study, some parameters with clinical and radiological information that have the potential to be risk factors in the WHO/ISUP nuclear grade of CCRCC determined by multivariate regression model were fed into ML model, and the radiomics features combined with the clinicoradiological characteristics showed a better performance for the discrimination of CCRCC grades.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that machine learning (ML)-based CT radiomics models can distinguish Fuhrman grade or WHO/ISUP grade of CCRCC (17,19,(28)(29)(30). However, most of these studies built ML models based on radiomics features only, neglecting the importance of clinical and radiological characteristics (17,19). The radiomics-derived data are not a panacea for computerized clinical decision- (35).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced CT examination revealed different information as time progressed. To the best of our knowledge, features extracted from full-phase or CMP combined with NP images are the most common objects of the ML-based radiomics model to predict the Fuhrman or WHO/ISUP grade of CCRCC (19,28,36,37). Huhdanpaa et al (38) found that absolute enhancement and residual enhancement in the NP phase are both more heterogeneous for low-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the previous studies on the prediction of nuclear grading of ccRCC by texture analysis have been based on the Fuhrman classification system, which has some inevitable inadequacies, such as interpretation difficulties and poor reproducibility in clinical applications (10,14). Besides the high application value for ccRCC, the WHO/ISUP nuclear grading is also a reliable prognosis indicator of patients with ccRCC (15).…”
Section: Discussionmentioning
confidence: 99%